Answer: [tex]x=\Large\boxed{\frac{m}{y-z} }[/tex]
Step-by-step explanation:
Given expression
[tex]z=y-\dfrac{m}{x}[/tex]
Subtract [ y ] on both sides
[tex]z-y=y-\dfrac{m}{x} -y[/tex]
[tex]z-y=-\dfrac{m}{x}[/tex]
Multiply [ -x ] on both sides
[tex](-x)(z-y)=(-x)(-\dfrac{m}{x} )[/tex]
[tex](x)(-1)(z-y)=m[/tex]
[tex](x)(y-z)=m[/tex]
Divide [ y - z ] on both sides
[tex](x)(y-z)\div(y-z)=m\div(y-z)[/tex]
[tex]x=\Large\boxed{\frac{m}{y-z} }[/tex]
Hope this helps!! :)
Please let me know if you have any questions